A safety, pharmacokinetic, pharmacogenomic and population pharmacokinetic analysis of the third‐generation EGFR TKI, olmutinib (HM61713), after single oral administration in healthy volunteers. Issue 4 (28th June 2019) - Noh, Young Su; Yoon, Seonghae; Kim, Suk Ran; Lee, Kyung‐Tae; Jang, In‐Jin
Abstract: The main objective of this phase I trial was to investigate pharmacokinetics (PKs) of olmutinib in three racial subjects. We also evaluate safety/tolerability and a population PK and pharmacogenomic analysis were performed for explorative purposes. A dose escalation study was conducted in 56 Korean, Japanese and Caucasian subjects. The food effect was assessed in the 300 mg Korean group. Individual PK parameters were calculated by non‐compartmental methods and presented by dose and race. Genotype analysis was performed using DMET ® plus to identify genotypes which affect PK characteristics. A population PK model was developed to explore inter‐individual variability and to evaluate the influence of possible covariates using NONMEM ® . T max was 2‐3 hour, regardless of race. The mean terminal half‐life ranged from 4.8 to 7.4 hour, with no significant differences between dose or racial groups. Dose‐normalized C max and AUClast were not significantly different between race groups. PK parameters were similar between the fasting and fed conditions. A single‐nucleotide polymorphism in the GSTM3 gene (rs4783) and a copy number variation in the GSTM1 gene were significantly related to AUC. A one‐compartment model with first‐order absorption adequately described the observed olmutinib data. Thirty adverse events were observed in 15 subjects, of which 26 events, all mild, were possibly related to olmutinib. A single oral dose of olmutinib 100‐300 mg was safe and well tolerated. PK parameters were dose‐proportional and did not differ by race. Food intake did not affect olmutinib absorption. Pharmacogenomic analysis indicated that glutathione S‐transferase might be involved in olmutinib metabolism.